Phenotyping of Adaptive Immune Responses in Inflammatory Diseases - Humrich, Jens Y.; Bernardes, Joana P.; Ludwig, Ralf J.; Klatzmann, David; Scheffold, Alexander (Frontiers in Immunology, 2020)
Immunophenotyping on the molecular and cellular level is a central aspect for characterization of patients with inflammatory diseases, both to better understand disease etiopathogenesis and based on this to develop diagnostic and prognostic biomarkers which allow patient stratification and tailor-made treatment strategies. Technology-driven developments have considerably expanded the range of analysis tools. Especially the analysis of adaptive immune responses, often regarded as central though mostly poorly characterized disease drivers, is a major focus of personalized medicine. The identification of the disease-relevant antigens and characterization of corresponding antigen-specific lymphocytes in individual patients benefits significantly from recent developments in cytometry and sequencing and proteomics. The aim of this workshop was to identify the important developments for state-of-the-art immunophenotyping for clinical application and precision medicine. We focused here on recent key developments in analysis of antigen-specific lymphocytes, sequencing and proteomics approaches, their relevance in precision medicine and the discussion of the major challenges and opportunities for the future.